PENGARUH KINERJA KEUANGAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PERUBAHAN HARGA SAHAM - Heru Susanto (Akademi Akuntansi YKPN Yogyakarta, 2013)
The objective of this study is to investigate the influence of financial performance and institutional ownership on stock price volatility. The performance measurements are using Debt to Equity Ratio (DER), Return on Equity (ROE) and Dividend Payout Ratio (DPR). The conflicting results of previous studies motivates researcher to re-examine the financial performance, institutional ownership and the influences of the interaction between institutional ownership and the financial performance on stock price volatility in public companies listed on Indonesian Stock Exchange (IDX). The results show that DER has a significant negative effect on stock price volatility ROE and DPR have a significant positive effect on stock price volatility. While institutional ownership has no significant effect on stock price volatility. The interaction between institutional ownership and financial performance (ROE) has a significant effect of stock price volatility.Keywords: debt to equity ratio, return on equity, dividend payout ratio, institutional ownership, stock price volatility.